2017
DOI: 10.18632/oncotarget.23810
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PD-L1 in esophageal squamous cell carcinoma: a meta-analysis

Abstract: Accumulated evidence has shown that the programmed cell death receptor 1/programmed cell death receptor 1 ligand 1 (PD-1/PD-L1) pathway is a promising therapeutic target for cancer immunotherapy. However, the association between PD-L1 and esophageal squamous cell carcinoma (ESCC) patient survival remains unclear. We performed a meta-analysis to investigate the prognostic value of PD-L1 in ESCC. We searched PubMed, Embase, Web of Knowledge, and Cochrane Central Register of Controlled Trials databases for releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 56 publications
(55 reference statements)
0
48
2
Order By: Relevance
“…PD‐L1 expression in TCs impairs T‐cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape . In several cancer types, such as HNSCC, oropharyngeal squamous cell carcinoma (SCC), pulmonary adenocarcinoma, oesophageal SCC, and urothelial carcinoma, PD‐L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD‐L1 expression in TCs impairs T‐cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape . In several cancer types, such as HNSCC, oropharyngeal squamous cell carcinoma (SCC), pulmonary adenocarcinoma, oesophageal SCC, and urothelial carcinoma, PD‐L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] In the present study, we investigated the immune environment in SDC, which is an an aggressive high-grade salivary malignancy, focusing on the immunoexpression of PD-L1, PD-1, the CTA PRAME, and MHC I. PD-L1 expression in TCs impairs T-cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape. 1,[33][34][35][36] In several cancer types, such as HNSCC, 12 oropharyngeal squamous cell carcinoma (SCC), 37 pulmonary adenocarcinoma, 38 oesophageal SCC, 39 and urothelial carcinoma, 40 PD-L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al reported that a high level of PD-L1 expression in TCs was associated with poor overall survival, DSS, and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…The TME was before divided into four classifications according to the expression of PD-L1 in tumor cells and the presence of TILs [ 38 ], thus the expression of checkpoints was included into immunoscore studies. Previous studies reported the relationship between PD-L1+ tumors and poorer prognosis in ESCC [ 39 , 40 ], however, they did not consider the expression of PD-L1 in TCs or ICs separately. This is the first time to investigate whether PD-L1 expressed by different cells has different prognostic values in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be ignored that some patients with tumours negative for PD-L1 also show a clinical response when treated with PD1/PD-L1 inhibitors (29). The strikingly heterogeneous PD-L1 expression in different PD-L1 IHC assays of the same tumour tissue may lead to the misclassi cation of patients who could be treated with PD1/PD-L1 inhibitors (30). In this regard, we attempted to assess the correlation and differences between the expression scores obtained by the SP263 and 22C3 assays.…”
Section: Discussionmentioning
confidence: 99%